Possibilities of prepectoral tissue expander placement at the first stage of two-stage breast reconstruction for cancer - Yu. S. Shatova; L. N. Vaschenko; N. A. Shevchenko; E. N. Chernikova; D. A. Gorokhova (Опухоли женской репродуктивной системы)
Background. The possibilities of the prepectoral two-stage reconstruction after mastectomy with tissue expanders without using other devices for covering are not clear and sometimes doubtful.Aim. To analyze the results of the first stage of breast prepectoral reconstruction with tissue expander without using other devices for covering. Namely, the frequency of early complications (seromas, protrusion/extrusion, infection), time for complete implant’s filling.Materials and methods. Retrospective review of 70 breast cancer patients, who underwent mastectomy with immediate breast reconstruction with textured expanders: 35 in prepectoral position (main group) and 35 in subpectoral position (control group). Inclusion criteria: no possibilities for breast-conserving surgery, indications for two-stage reconstruction and patient’s agreement. Extra criteria for the main group: rather good thickness of subcutaneous fat (PINCH-test ≥1.5 cm), no scars in operation region, good perfusion of flaps after mastectomy. Expansion with saline were in operation room firstly following it each 7–14 days. All expanders have been filled to the moment of direct results were estimated.Results and conclusion. Prepectoral position of tissue expander without using other devices for covering don’t rise the long-term seroma frequency, necessary time of postoperative drainage and expander loss risk (p ˃0.05). More comfortable and fast expander expansion to required volume in main group was the clear profit (p ≤0.05). Thus, according to our preliminary results prepectoral implantation of tissue expander without using other devices for covering in two-stage breast reconstruction after mastectomy can be the adequate choice in some patients.